Releitura da função sócioambiental do parque de exposições Jayme Canet Junior - Francisco Beltrão - PR - Modanese, Ione Aparecida Zucchi (2010)
The present work accomplishes a case study of Jayme Canet Junior Park, rereading the socioenvironmental function while searching fundaments to comprehend the relationship with public parks and its interrelations with urban parks. We have realized a diagnostic of the socioenvironmental conditions that Jayme Canet Junior Park has, we have done laboratorial exams of Urutago brook´s water, setting up vegetation condition and riparian forest, beyond perform a memorial according to the physical structure, its process of creation, besides that, we have studied the place as a space of leisure, Conservation Unit and to develop an informal Environment Education. As well, we have aborted facts related to work, free time and leisure in the perspective that capital and labor interfere directly in the way of living from those who attend the Park. In addition to it some different bias were developed about multiple concept of nature in the perspective of classic thinkers as Descartes, Leibniz, Humboldt, Kant, Bacon and Marx, considering Human history, its culture and the relations established with society/nature through history. We have analyzed some public s environment politics that were created and developed in Brazil since the 70´s and how these politics have influenced in Environment Educations practices and in the generation of nature concepts.